Blaze produced by a dual-period array of subwavelength cylinders - Lester, Marcelo Fabian (2009)
We propose an alternative way of enhancing the intensity diffracted by a grating in a given direction using a dual-period array. Each period comprises several identical cylinders with diameters much smaller than the incident wavelength (subwavelength cylinders), whose axes are aligned in a plane which is tilted with respect to the periodicity direction. We present results for metallic and dielectric cylinders, and show that in both cases this structure behaves like a blazed grating in the sense of its capability to enhance the intensity in a pre-designed direction. This blazed-like behavior is found for both incident polarization modes. If we consider the quick evolution of manufacturing techniques of nanogratings, such structures constitute a realizable alternative not only for the microwave and millimeter wave regions but also for optical devices. © 2009 IOP Publishing Ltd.